Ultramorphology of the digestive tract of Paratrechina longicornis (hymenoptera, formicidae) - Solis, D. R. [UNESP]; Caetano, F. H. [UNESP]; Yabuki, A. T. [UNESP]; Moretti, T. C. [UNESP]; Bueno, O. C. [UNESP] (My University, 2009)
The digestive tract of ants is basically similar to that of other hymenopterans. Nevertheless, there are regions that vary considerably, and this could be used in the taxonomy of subfamilies and genera. Herein, we have morphologically described the digestive tract of Paratrechina longicornis (Latreille) through Scanning Electron Microscopy (SEM). Five queens and ten workers had their digestive tracts dissected and prepared for SEM analyses. It proved to be very similar to the digestive tract of Camponotus (Mayr) ants, except for the number of Malpighian tubules and rectal pads. Workers of P. longicornis have six tubules arranged in a single row and their queens presented eighteen tubules arranged in two rows. The number of tubules also varies according to the size of the specimens and ant species, although there seems to be no pattern to it. In the rectum, we found two rectal pads, a number different from that usually found in other Formicinae (six rectal pads). It seems that this number might be related to an ongoing process of general reduction of size and number of these pads. The obtained results may contribute to taxonomy and feeding behaviour studies.
Keywords: Crazy ant; Digestive tract; Formicinae; Insecta; Ultramorphology